La protesta feminista #8M 2020 en México a través de la participación de comentarios en YouTube - García-González, Lidia A. (2020)
The present article is a quantitative study of the comments generated and published by users on March 8 and 9 on the YouTube video platform, about the International Women’s Day on March 8, 2020, known as #8M in Mexico City. Its purpose is to know what kind of issues, discussions and perceptions revolve around one of the most attended feminist demonstrations against gender violence and impunity in the face of a growing wave of femicide in Mexico. It also presents a discussion on the potential and risks of YouTube for cyber-feminism and protest, based on comments generated by users. The results show a space in which a strong misogyny, a high misunderstanding of feminism and the impossibility of a productive and dialogic conversation are manifested.